Franjas urbanas em cidades novas : o caso de Maringá - Paraná - Pereira, Juliana Alves (2011)
This paper aims to ascertain the existence and characteristics of urban fringe belts in a planned new town. M. R. G. Conzen debugged the concept of urban fringe belts, designed by Hebert Louis by the observation of medieval cities. His analysis consists of the physical configuration of urban development, envisioned in the concentration of public services and institutions at the periphery of urban form, which constitutes urban fringe belts. These are alternately displayed with residential areas. However, the possible existence of urban fringe belts in a sixty-two year old planned new town suggests a slightly different case. Thus, a particular analysis method was adapted to the reality of Maringa, Brazil. Public facilities and private lots of low occupancy were considered. The urban fringes were then signaled on subsequent maps of urban development which allowed representing the emergence, stagnation and modifying of urban fringe belts in five periods of urban growth. As a results showed that, despite the peculiarities of a new city, is possible to identify urban fringe belts. In Maringá it's also noticed two distinct formations: urban fringe belts more consistent, formed by zoning and; urban fringe belts of institutional use that arise accompanying urban growth.